Impact of zero tillage maize production on yield, income, and resource utilization in peninsular India: an action-based quasi-experimental research - Dey, Shiladitya; Abbhishek, Kumar; Saraswathibatla, Suman; Singh, Piyush Kumar; Kuntamalla, Sreedhar; Bommaraboyina, Prithvi Ram; Raj, Abhishek; Kaliki, Hamika; Choubey, Abhishek Kumar; Rongali, Hari Babu; Upamaka, Aruna (Frontiers in Sustainable Food Systems, 2024)
The present study aims to identify the crucial determinants of the widespread adoption of zerotillage (ZT) technology in maize production. The study also measures the impact of ZT adoption on maize yield, income generation, and the expenses associated with different agricultural operations.The study used multi-stage stratified random sampling and conducted a face-to-face questionnaire survey to collect primary data from 1189 maize farmers. Initially, the study employed probit regression analysis to identify the ZT adoption determinants. Subsequently, using the Propensity Score Matching (PSM) approach, the study measures the impact of ZT adoption over conventional tillage in terms of yield, income, and cost management. Finally, the Endogenous Switch Regression (ESR) method was implemented to mitigate unobserved heterogeneity and sample selection bias. Additionally, ESR assessed the robustness of PSM results.The probit model identifies that variables like education, institutional credit adoption, crop insurance, visit of extension agent, landholding size, and prior experience of new technology adoption positively influence ZT adoption. The PSM and ESR approach results suggest that ZT adoption positively impacts farmers' yield and net income while reducing the cultivation cost and labor use. Results show that ZT adoption decreases the cost of land preparation, weed, pest management, and harvesting, thereby decreasing the cultivation cost by INR8376 acre -1 . Moreover, adopting ZT improves maize yield by 2.53quintal acre -1 and minimizes 9.56 persondays acre -1 .The study findings may support policymakers in designing suitable agricultural policies to improve technology adoption and motivate farmers for sustainable production.